The Importance of Civic Education Learning on Nationalism in the Era of Globalisation - Mas Fierna Janvierna Lusie Putri; Herdi Wisman Jaya; Fidah Nurbayti; Dona Purnama; Yeti Yetnasari (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract In this era of globalization, there are negative and positive impacts that can significantly affect the character or identity of Indonesian society, especially the younger generation and the loss of a sense of nationalism or love for the Republic of Indonesia. Therefore, Civic Education is the basis for the younger generation in Indonesia in responding to the negative impacts of globalization. This research uses a library method that is looking for reliable sources such as scientific journals, research articles and descriptive reports that are relevant. The results of this study indicate that the role of Civic Education is very important for the Indonesian state in this era of globalization, which aims to preserve the character or identity of the Indonesian state and be able to compete with foreign cultures. This has proven to be very important for the Indonesian people, such as the Indonesian people being able to think critically, have innovative and creative and of course obey the rules that apply in Indonesia. Therefore, understanding the role of civic education through the education sector requires synergy between all stakeholders. This will be the main capital needed in the current era of globalization. The term globalization is not a new term or a term of the day. Globalization can also be defined as the process of entering into a world that affects all important aspects of human life. Keyword: Civic Education, Nationalism Attitude, Nationalism in the era of globalization